Enhanced platelet reactivity in pediatric depression: an observational study - Can, Mehmet M; Guler, Gamze; Guler, Ekrem; Ozveren, Olcay; Turan, Burak; DiNicolantinio, James J; Kipshidze, Nodar; Serebruany, Victor (Blood coagulation & fibrinolysis, 2015)
Depression is associated with poor prognosis for cardiovascular disease (CVD) including mortality. Among multiple mechanisms linking depression and CVD, changes in platelet reactivity are known to be one of the major confounders of such adverse association. However, there are very limited data in children. Thus, we evaluated some conventional hemostatic indices including whole blood platelet aggregation in patients with documented pediatric depression and compared these data with those obtained from healthy children. The pediatric patients fulfilled criteria for major depression with a minimum score of 19 on the 21-item Beck Depression Inventory Scale. Plasma fibrinogen, D-dimer, platelet count, mean platelet volume, and platelet aggregation induced by ADP and collagen were measured in 67 pediatric patients with depression and matched by age and sex with 78 healthy controls. As expected, the depressed children had significantly higher BECK scales (P = 0.001) compared with the normal subjects. Platelet aggregation induced by ADP and collagen (P = 0.0001 for both) was significantly higher in depressed children. BECK scale scores correlated significantly with platelet aggregation induced by ADP (r = 0.3, P = 0.001) and collagen (r = 0.4, P = 0.01). In contrast, platelet counts, fibrinogen, D-dimer, mean platelet volume, and antithrombin-III levels were almost identical between both groups. Children with depression exhibit mostly intact hemostatic parameters, with the exception of significantly higher platelet activity when compared with healthy controls. These data match well with prior evidence from depressed adults supporting the hypothesis that platelets participate in the pathogenesis of depression. However, beyond pure assessment of platelet activity, other elements including serotonin content and cell receptor changes in pediatric depression should be elucidated before randomized trial(s) can be justified.